Biological Control Potential of Two Steinernematid Species Against the Date Fruit Stalk Borer (Oryctes elegans Prell, Coleoptera: Scarabaeidae). Issue 3 (20th June 2018) - Atwa, Atwa A
Abstract: The fruit stalk borer ( Oryctes elegans ) is an important pest of date palm ( Phoenix dactylifera ) trees in Saudi Arabia. This study was conducted to determine efficacy of using two species of entomopathogenic nematodes, Steinernema kushidai and Steinernema glaseri, against O. elegans under laboratory and field conditions. Under laboratory conditions, both species of nematodes showed a significant effect on the mortality of O. elegans larvae. Significant variations were observed when insects were exposed to nematodes for variable durations under laboratory conditions. They showed no differences in insect larval mortality when tested either in aqueous suspensions or in Galleria -infected cadavers. Insects exposed to nematode aqueous suspension for 4 d and those treated with Galleria -infected cadavers showed the same rates of mortality, which differed when insects were exposed to nematode-infected cadavers under field conditions. Mean percentages of corrected mortality varied between nematode species and number of infected cadavers. S. kushidai caused significantly higher mortality percentages ± SE (72.17 ± 5.57, 95.83 ± 4.17, 94.43 ± 5.57, and 100%) compared with S. glaseri when the fruit stalk borer, O. elegans, was treated for 6 wk with two, four, six, and eight infected cadavers, respectively.